Taking Stock, Reprise - van Herk, Aritha (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2016)
This essay examines the 1978 Calgary Conference on the Canadian Novel, and the publication that emerged from it entitled Taking Stock, as a moment that distills the ongoing tabulation of Canadian literature in various lists and inventories that seek to identify and anoint significant works. It focuses on two speakers at that conference, Robert Kroetsch and Marian Engel, as examples of major writers who are still read but who are gradually disappearing from contemporary cultural awareness, despite their important contributions to the development of the Canadian canon. Engel and Kroetsch participated in an important moment in Canadian literary history; Engel’s Bear and Kroetsch’s The Studhorse Man embody a sense of what Canadian literature aspired to, but those works also foreshadow the evolution of Canadian fiction. Their authors straddle the penumbra of the last forty years, and how Canadian literature bloomed, matured, and now seems to withdraw not from its continuing bravura performance in the global literary world, but from its own memory and recognition of those early pathfinders. Their works speak to the paradox of Canadian writing as ironically unaware of its own invention.